2003
DOI: 10.1038/sj.bjp.0705471
|View full text |Cite
|
Sign up to set email alerts
|

N‐Salicyloyltryptamine, a new anticonvulsant drug, acts on voltage‐dependent Na+, Ca2+, and K+ ion channels

Abstract: 1 The aim of this work was to study the effects of N-salicyloyltryptamine (STP), a novel anticonvulsant agent, on voltage-gated ion channels in GH3 cells. 2 In this study, we show that STP at 17 mM inhibited up to 59.2710.4% of the I to and 73.178.56% of the I KD K þ currents in GH3 cells. Moreover, the inhibitory activity of the drug STP on K þ currents was dose-dependent (IC 50 ¼ 34.678.14 mM for I to ) and partially reversible after washing off. 3 Repeated stimulation at 1 Hz (STP at 17 mM) led to the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
2
9
0
1
Order By: Relevance
“…ethosuximide). 23 Furthermore, Araújo et al 24 have demonstrated that NST promotes the blockade of sodium channels from GH3 cells, corroborating with the results of this work. However, the alteration produced by NST on the time constant of repolarization could also indicate a possible involvement of voltage-gated potassium channels, as was verified by Pisciotta and Prestipino 25 when fenitoine was used.…”
Section: Discussionsupporting
confidence: 89%
“…ethosuximide). 23 Furthermore, Araújo et al 24 have demonstrated that NST promotes the blockade of sodium channels from GH3 cells, corroborating with the results of this work. However, the alteration produced by NST on the time constant of repolarization could also indicate a possible involvement of voltage-gated potassium channels, as was verified by Pisciotta and Prestipino 25 when fenitoine was used.…”
Section: Discussionsupporting
confidence: 89%
“…Throughout this review we showed the complex pharmacological profile of eugenol in blocking different ion channels. Interesting to note is the fact that other anticonvulsant substances seems to exert its effects via multiple mechanisms Araujo et al (2003). From a functional viewpoint, the simultaneous action of eugenol over distinct ion channels may prevent the ability of neuronal cells to trigger action potentials and therefore makes it very attractive as an anticonvulsant agent.…”
Section: Constituents Of Essential Oils That Acts In the Central And mentioning
confidence: 99%
“…Because they are easily cultivated in the laboratory, our patch clamp experiments performed to measure calcium currents were carried out on those neuroendocrine cells. This investigation was done using barium as the charge carrier through the L-type calcium channel (Araújo et al, 2003). AqEx reduced in 30 % this inward current without changing the peak of the current-voltage curve.…”
Section: Discussionmentioning
confidence: 99%